SOFTWARE DEVELOPMENT PROJECT MANAGEMENT BASED ON WORK BREAKDOWN STRUCTURE AND ODOO ERP - Supriyono, Supriyono; Chasanah, Nur (Informatika, Universitas Jenderal Soedirman, 2023)
Software Development Project Management is the most important part of the Software Development Life Cycle process. The stages in project development include Initiating, Planning, Executing, Monitoring and Controlling, and Closing. This research uses the Work Breakdown Structure approach, which is a method used in project management to break down complex work into smaller and more manageable parts. Work Breakdown Structure helps in organizing, classifying, and describing the work to be done in a project. Odoo ERP is part of the tools that can be used for project management. Testing the project module using Blackbox Testing. The test scenario includes functional testing of the project management module. Application testing shows good results and is following existing needs. The results show that software project management using the Work Breakdown Structure approach can be implemented properly with Odoo ERP tools.